A novel shared control algorithm for industrial robots. (26th December 2016) - Ramacciotti, Marco; Milazzo, Mario; Leoni, Fabio; Roccella, Stefano; Stefanini, Cesare
Human management of robots in many specific industrial activities has long been imperative, due to the elevated levels of complexity involved, which can only be overcome through long and wasteful preprogrammed activities. The shared control approach is one of the most emergent procedures that can compensate and optimally couple human smartness with the high precision and productivity characteristic to mechatronic systems. To explore and to exploit this approach in the industrial field, an innovative shared control algorithm was elaborated, designed and validated in a specific case study.